Yanson point-contact spectroscopy of Weyl semimetal WTe2 - Naidyuk, Yu G.; Bashlakov, D. L.; Kvitnitska, O. E.; Aswartham, Saicharan; Morozov, Igor; Chernyavskii, I. O.; Shipunov, Grigory; Fuchs, G.; Drechsler, S-L; Huehne, R.; Nielsch, Kornelius; Buechner, B.; et al. (2D Materials, 2019)
We carried out point contact (PC) investigation of WTe2 single crystals. We measured Yanson PC spectra (d 2 V/dI 2) of the electron-phonon interaction (EPI) in WTe2. The PC spectra demonstrate a main phonon peak around 8 meV and a shallow second maximum near 16 meV. Their position is in line with the calculation of the EPI spectra of WTe2 in the literature, albeit phonons with higher energy are not resolved in our PC spectra. An additional contribution to the spectra is present above the phonon energy, what may be connected with the peculiar electronic band structure and need to be clarified. We detected tiny superconducting features in d 2 V/dI 2 close to zero bias, which broadens by increasing temperature and blurs above 6 K. Thus, (surface) superconductivity may exist in WTe2 with a topologically nontrivial state. We found a broad maximum in dV/dI at large voltages (>200 mV) indicating change of conductivity from metallic to semiconducting type. The latter might be induced by the high current density (∼108 A cm-2) in the PC and/or local heating, thus enabling the manipulation of the quantum electronic states at the interface in the PC core.
CRIS-Team Scopus Importer:2022-04-14
Keywords: electron phonon interaction; superconductivity; Weyl semimetals; WTe; Yanson point-contact spectroscopy